2015
DOI: 10.1186/s12969-015-0041-9
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of sensorineural hearing loss in Muckle-Wells-syndrome

Abstract: BackgroundMuckle-Wells-syndrome (MWS) is an autoinflammatory disease characterized by systemic and organ-specific inflammation due to excessive interleukin (IL)-1 release. Inner ear inflammation results in irreversible sensorineural hearing loss, if untreated. Early recognition and therapy may prevent deafness. The aims of the study were to characterize the spectrum of hearing loss, optimize the otologic assessment for early disease and determine responsiveness to anti-IL-1-therapy regarding hearing.MethodsA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 33 publications
0
44
0
Order By: Relevance
“…Other observational studies have also shown the effectiveness of canakinumab in improving the Disease Activity Score (DAS), 57 65 Autoinflammatory Disease Activity Index (AIDAI) score, 36 83 complete/partial resolution of symptoms, 38 45 88 improvement in physician/patient assessed PROs 36 65 85 and the Child Health Assessment Questionnaire (CHAQ). 65 Of the eight studies assessing other outcomes, 23 42 45 47 5557 65 treatment with canakinumab was associated with improvement or stabilisation in neurological outcomes (eg, migrainous headache), 23 42 45 hearing loss, 23 42 5557 65 vision outcomes (eg, uveitis, conjunctivitis) 23 47 and musculoskeletal outcomes. 23…”
Section: Resultsmentioning
confidence: 99%
“…Other observational studies have also shown the effectiveness of canakinumab in improving the Disease Activity Score (DAS), 57 65 Autoinflammatory Disease Activity Index (AIDAI) score, 36 83 complete/partial resolution of symptoms, 38 45 88 improvement in physician/patient assessed PROs 36 65 85 and the Child Health Assessment Questionnaire (CHAQ). 65 Of the eight studies assessing other outcomes, 23 42 45 47 5557 65 treatment with canakinumab was associated with improvement or stabilisation in neurological outcomes (eg, migrainous headache), 23 42 45 hearing loss, 23 42 5557 65 vision outcomes (eg, uveitis, conjunctivitis) 23 47 and musculoskeletal outcomes. 23…”
Section: Resultsmentioning
confidence: 99%
“… In a series of patients with MWS (52% of whom were children), 100% exhibited high‐frequency SNHL (equal to or above 6 kHz), whereas 74% were affected from 500 to 4,000 Hz, and all had normal caloric function. Interleukin‐1 inhibition resulted in stable or improved hearing in 96% of the patients, although improvement was noted in only 24% and was worsening in 4% . Interestingly, MWS may also comprise neurologic sequelae, including migraine, despite a negative magnetic resonance imaging; symptoms were controlled with IL‐1 antagonism .…”
Section: Methodsmentioning
confidence: 99%
“…A recent study where CAPS patients underwent detailed auditory testing found that 100% of symptomatic CAPS patients had high frequency pure tone averages abnormalities, whilst 74% had an abnormal assessment focusing on standard frequencies (0.5–4 kHz) [ 26 ]. Encouragingly, treatment with IL-1 blockade resulted in improved or stable hearing in 91% of patients [ 26 ]. However, it is important to note that once sensorineural damage has occurred, hearing dysfunction is likely irreversible.…”
Section: Management Of Capsmentioning
confidence: 99%